Influence of simulation and clinical settings on peripheral vein cannulation skill learning in nursing education: A qualitative study - Monika Ravik; Ida Torunn Bjørk (Elsevier, 2023)
Background: Peripheral vein cannulation is a complex yet common practical skill. Learning to insert a peripheral vein cannula is fundamental in nursing education; however, the most beneficial pedagogical approaches are yet to be elucidated. Objective: To explore and impart a deeper understanding of the learning conditions in nursing education for developing competency in peripheral vein cannulation. Design: Qualitative, explorative. and comparative research design Setting(s): Two nursing educational settings in southern Norway: an academic setting for simulation-based peripheral vein cannulation skill learning, followed by a hospital setting that provided a 9 week clinical placement period. Participants: Nine student nurses in the second year of a bachelor's programme in nursing. Methods: Focus group interviews, individual interviews, and ad hoc conversations with the student nurses on their experiences during and after the process of developing competency in peripheral vein cannulation. Thematic analysis was used to identify categories and common themes. Results: Eight major themes were identified: 'Anatomical and physiological conditions related to the training modalities', 'Realism in training', 'Sequences in peripheral vein cannulation training', 'Different training modalities affording varied learning opportunities', 'Professional nursing assessments', 'Patients' and peers' emotional reactions', 'Student nurses' own emotional reactions', and 'Significance of the relationship between the student nurse and patient'. Conclusions: Simulation-based peripheral vein cannulation practice was an important starting point for the students' skill learning. However, the students experienced the complexity of the skill only in the clinical setting because it offered several learning opportunities. Nonetheless, our findings indicate a need to further review peripheral vein cannulation skill learning, especially patient contributing factors, to enhance the transfer of learning from the simulation setting to the clinical setting. Tweetable abstract: Clinical setting-based peripheral vein cannulation practice is vital for student nurses' skill learning because of the skill's complexity